FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN PETANI GARAM KAWASAN PESISIR KABUPATEN REMBANG - Rikah Rikah; Novi Kusumaningsih (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2018)
One of the main issues faced by community salt farmers in the coastal area of Rembang Regency is the low level of welfare of community salt farmers due to the low level of income of the people of salt farmers. The low level of productivity, land ownership, work experience, education, marketing and capital are the main factors that can result in low levels of income for the salt farmers to improve their welfare.This study uses the Multiple Linear Regression Analysis method. The population in this study included all community salt farmers in the coastal area of Rembang Regency. According to records from the 2015 Marine and Fisheries Service Office, there were 1,240 salt farmers. The sampling technique in this study used cluster sampling. The results of this study are for variables Productivity, Land Area and Education Level of salt farmer owners have a significant positive effect. Where as for the variables of Marketing, Capital and Working Experience there is no significant positive effect.